Transformasi Potensi Kelapa Lokal melalui Sosialisasi Pembuatan VCO di Nagari Sungai Jambur - Armida S; Yola Syaflina; Sandy Pratama; Imraatun Nazhifah; Vanesa Ayudia Ashatilla (LP3M Universitas Putra Bangsa, 2025)
Indonesia has significant potential in coconut production, with a land area reaching 3.7 million hectares and annual production exceeding 2.8 million tons. In West Sumatra, coconut processing is still traditional, thus not optimally increasing the economic value of the community. This community service activity aims to improve the skills of Nagari Sungai Jambur residents in processing coconuts into high-value Virgin Coconut Oil (VCO). The method used is descriptive qualitative through observation and interviews. The training was conducted in three sessions: socialization of the benefits and process of VCO production, hands-on practice, and product filtration after 24 hours of fermentation. The results showed active community participation and the successful production of clear, distinctive-flavored VCO. This activity not only increased community knowledge and skills but also opened up new business opportunities based on local potential. This training directly supports the achievement of the Sustainable Development Goals (SDGs), specifically SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), and SDG 12 (Responsible Consumption and Production).